Enhancing Teacher Performance through Capacity Building: A Comprehensive Analysis of Professional Development, Mentoring, and Organizational Support - Putra, Rizaldi; Renaldo, Nicholas; Purnama, Intan; Putri, Novita Yulia; Suhardjo, Suhardjo (Reflection: Education and Pedagogical Insights, 2024)
This research examines the impact of capacity-building initiatives on teacher performance, focusing on the role of professional development, mentoring, and resource availability. Through a mixed-methods approach involving surveys and interviews, the study identifies a significant positive relationship between capacity-building efforts and improved teaching effectiveness. The research integrates various theoretical frameworks, including Andragogy, Social Cognitive Theory, and the Resource-Based View, to understand how these initiatives enhance teachers' confidence, classroom management, and student engagement. However, the study also highlights challenges such as time constraints, inadequate funding, and insufficient administrative support, which can hinder the effectiveness of capacity-building programs. The findings emphasize the need for continuous institutional support and the strategic integration of capacity-building efforts to foster sustainable improvements in teaching practices. Recommendations include increasing access to tailored professional development, integrating mentoring into capacity-building programs, and regularly evaluating the impact of these initiatives on teacher performance.